Developing a question prompt list for the oncology setting: a scoping review - Schulte-Vieting, Tamara; Siegle, Anja; Jung, Corinna; Villalobos Bollen, Matthias Americo; Thomas, Michael (Patient education and counseling, 2022)
Objective - The purpose of this study was to provide an overview of existing methods used to develop a Question Prompt List (QPL) for an oncology setting. - Methods - We conducted a search of the literature published between 1999 and 2019 in five online databases followed by a hand search, and extracted data on the methods used to develop a QPL. - Results - A total of 21 studies were included. The review shows differences in the development of older QPLs (1999-2009) and current QPLs (2010-2019). However, most QPLs were developed using interviews or focus groups with patients and an expert session to review or adapt the QPL. Health professionals, patients, and researchers were included in nearly all the studies. - Conclusion - To develop a QPL, it is important to combine several information sources and at least to involve health professionals, patients, and researchers in the development process. Review or evaluation steps can improve the appropriateness and acceptance of a QPL. - Practice implications - Further research is needed to define the type of target population for new QPLs and to develop a framework for their development.